2017
DOI: 10.1016/j.acvd.2016.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognosis of infective endocarditis in children: Insights from a Tunisian multicentre registry

Abstract: In the Tunisian context, IE in children is still characterized by the high prevalence of RHD as an underlying heart disease. Short- and long-term mortality rates remain high. Heart failure, acute renal failure and neurological complications are significantly associated with death at 6-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
2
16
1
1
Order By: Relevance
“…Outcome data were reported in 23 (55%) of 42 studies. [21][22][23][25][26][27][28][29][31][32][33]35,[40][41][42][45][46][47][48][49][50][51][52] The pooled in-hospital mortality rate across studies was 22•6% (95% CI 19•5-25•9), which was similar in studies from north Africa (22•5%) and those from sub-Saharan Africa (22•7%; figure 4). Heart failure was the most frequent complication, occurring in 47 5 and the appendix (pp 62-66).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Outcome data were reported in 23 (55%) of 42 studies. [21][22][23][25][26][27][28][29][31][32][33]35,[40][41][42][45][46][47][48][49][50][51][52] The pooled in-hospital mortality rate across studies was 22•6% (95% CI 19•5-25•9), which was similar in studies from north Africa (22•5%) and those from sub-Saharan Africa (22•7%; figure 4). Heart failure was the most frequent complication, occurring in 47 5 and the appendix (pp 62-66).…”
Section: Resultsmentioning
confidence: 86%
“…22,[29][30][31]36,38,43 A microorganism was detected in 48 Twelve (29%) of 42 studies reported data for surgical treatment of infective endo carditis. [21][22][23]25,26,28,29,31,40,42,45,52 The rate of surgery uptake in studies from north Africa was 49•7% (95% CI 42•5-56•9), ranging from 30•2% to 64•6%, whereas the rate of surgery uptake in two studies from sub-Saharan Africa was 46•1% (39•0-53•4). The pooled rate of surgical treatment of infective endocarditis was 49•1% (95% CI 43•2-55•1; appendix p 56).…”
Section: Resultsmentioning
confidence: 98%
“…In this study, they stated that 93.67% of the possible IE cases met the definite IE criteria when there was major culture-positive microbiological evidence, and if the cases were culturenegative, 32.85% of definite IE cases could be considered as possible IE; thus, they wanted to emphasize the importance of major culturepositive microbiological criteria for a clinical diagnosis. In these and many other studies, antibiotic treatments given prior to obtaining blood samples were reported as the most important cause of culture negativity (19,20). Walid Jomaa et al (20), in their study on the prognosis and epidemiological features of IE in Tunisian children, were able to detect reproductive IE-compatible microorganisms:…”
Section: Discussionmentioning
confidence: 94%
“…In these and many other studies, antibiotic treatments given prior to obtaining blood samples were reported as the most important cause of culture negativity (19,20). Walid Jomaa et al (20), in their study on the prognosis and epidemiological features of IE in Tunisian children, were able to detect reproductive IE-compatible microorganisms:…”
Section: Discussionmentioning
confidence: 94%
“…Aunque la endocarditis en pediatría no es una enfermedad frecuente, los informes mundiales indican una elevada mortalidad por esta causa, sobre todo cuando se aíslan cepas de S. aureus. En uno de los estudios, la mortalidad fue muy elevada y hubo una diferencia estadísticamente significativa con respecto a los pacientes sin endocarditis, lo que ya se ha evidenciado en estudios similares (6,17,18).…”
Section: Discussionunclassified